2018
DOI: 10.1007/s00068-017-0897-0
|View full text |Cite
|
Sign up to set email alerts
|

Accidental hypothermia as an independent risk factor of poor neurological outcome in older multiply injured patients with severe traumatic brain injury: a matched pair analysis

Abstract: Accidental hypothermia seems to have a negative impact on neurological recovery in older patients with multiple injuries including traumatic brain injury which outweighs potential benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…In the current review, two studies reported significantly higher transfusion requirements [7,31] and two other studies significantly higher INR values [39,41] in hypothermic patients compared to normothermic patients.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…In the current review, two studies reported significantly higher transfusion requirements [7,31] and two other studies significantly higher INR values [39,41] in hypothermic patients compared to normothermic patients.…”
Section: Discussionmentioning
confidence: 65%
“…In the current review, two studies reported significantly higher transfusion requirements [ 7 , 31 ] and two other studies significantly higher INR values [ 39 , 41 ] in hypothermic patients compared to normothermic patients. In the setting of severely injured trauma patients, higher transfusion requirements and INR values may serve as surrogate markers for coagulopathy.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations